The nanocomposite system comprising folic acid-modified graphene quantum dots loaded with evodiamine in the treatment of oral squamous cell carcinoma. (August 2022) - Ma, Yu; Liu, Yan; Wang, Yurui; Guo, Yanzhu; Li, Yuanyuan; Li, Ruizhi; Kong, Xinzi; Han, Qize; Wei, Rong; Wang, Jing
Graphical abstract: GQDs-FA-EVO self-assembly synthesis process, targeting and drug treatment, and tumor labeling. Highlights: The GQDs-FA-EVO nanocomposite system improved the selectivity of EVO to cancer cells, making the efficient loading of EVO possible to synergistically target the treatment of OSCC. When the loading of EVO into the composite system was 10%, the growth inhibition rate of OSCC cells exceeded 50%. In tumor-bearing nude mice, the nanocomposite loaded with 10% EVO significantly reduced the tumor volume by 19% compared to the EVO group. The self-assembly method for the preparation of GQDs-FA-EVO nanocomposite systems is a simple means to realize spontaneous reactions using ambient thermal energy. Molecular dynamics simulation techniques predict and guide the fabrication of GQDs-FA-EVO nanocomposite systems. This work provides a scientific basis for the development of similar composite systems. Highlighting the possibilities of this system and others alike in the synergistic targeted therapy of OSCC. Abstract: Oral squamous cell carcinoma (OSCC) is one of the most common malignant tumors in the world. At present, drugs are one of the most indispensable means to treat OSCC. Evodiamine (EVO) is one of the major bioactive compounds of the plant Evodia and has been shown to inhibit the growth of OSCC cells. However, it suffers from poor aqueous solubility, which results in a low bioavailability. To improve of this property, we utilized graphene quantum dots (GQDs) as a vehicle for the delivery of EVO, which were functionalized with folic acid (FA) for targeting the tumor cells. The GQDs-FA-EVO nanocomposite system was synthesized by a self-assembly method, which was simulated theoretically at the atomic scale using molecular dynamics calculations. These MD simulations confirmed that the binding of EVO to the FA-functionalized GQDS was spontaneous and resulted in the formation of a highly stable nanocomposite complex. When the loading of EVO into the composite system was 10%, the growth inhibition rate of OSCC cells exceeded 50%( p < 0.01). In tumor-bearing nude mice, the GQDs-FA-EVO composite loaded with 10% EVO significantly reduced the tumor volume by 19% compared to the EVO group after the 18-days treatment( p < 0.05).